УСТРОЙСТВА ГАРАНТИРОВАННОГО ПИТАНИЯ С ПОЛУПРОВОДНИКОВЫМИ ПРЕОБРАЗОВАТЕЛЯМИ - Юрченко, О.Н.; Гречко, А.Э. (Інститут електродинаміки НАН України, Київ, 2014)
Schematics described construction of uninterruptible power supply devices (UPSD) using a three-level and three-level power pulse-width converter and autonomous voltage inverter. UЗSD built through the two routes of electric guaranteed energy supply tires. It is shown that the introduction of the three-level PWC and AVI allows you to extend the functionality of the device as a consequence of improving the quality of their output voltages and power indicators. The analysis of building UPSD more rational in terms of improving their energy and weight and size by eliminating channel additional power backup energy conversion DC to DC is shown. The introduction of the three-level AVI reduces almost twice the operating voltage power transistors. References 2, figures 3.